2009
DOI: 10.1002/jemt.20788
|View full text |Cite
|
Sign up to set email alerts
|

Autophagosomal glycogen‐degrading activity and its relationship to the general autophagic activity in newborn rat hepatocytes: The effects of parenteral glucose administration

Abstract: The effects of the administration of parenteral glucose on the postnatal glycogen autophagic activity and its relationship to the general autophagic activity, were studied in newborn rat liver using electron microscopy and biochemical methods. Glucose abolished the normal postnatal hypoglycemia and preserved the hepatocytic hyaloplasmic glycogen to the levels of birth. It also inhibited the normal postnatal increase in the number and volume of autophagic vacuoles. Glucose especially decreased the rate of postn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…95649) were from Fluka (Athens, Greece). D ‐Glucose, 3MG, and propranolol hydrochloride 1 mg/mL ready solution (Inderal) were obtained as before (Kalamidas and Kondomerkos,2010; Kondomerkos et al,2004).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…95649) were from Fluka (Athens, Greece). D ‐Glucose, 3MG, and propranolol hydrochloride 1 mg/mL ready solution (Inderal) were obtained as before (Kalamidas and Kondomerkos,2010; Kondomerkos et al,2004).…”
Section: Methodsmentioning
confidence: 99%
“…The liver glycogen‐hydrolyzing activity of acid α‐1,4‐glucosidase is also inhibited, and the hepatocytic autophagic vacuoles show increased amounts of undigested glycogen evidently due to the impaired glycogen autophagic activity (Kalamidas et al,1994; Kondomerkos et al,2005; Kotoulas et al,1971,2004). In a previous study, preliminary evidence suggested that the inhibitory effect of glucose on acid glucosidase depended, at least partly, on glucose phosphorylation (Kalamidas and Kondomerkos,2010). In this study, the effects of administration of two glucose analogs, the nonmetabolizable 3‐methylglucose (3MG) or the not fully metabolizable 2‐deoxyglucose (2DG), were studied.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Most of the recent work on liver autophagy has focused on lipid digestion (lipophagy) (11,12) and glycogen digestion (13). There are few studies of liver lysosomal enzymes that act upon proteins and sulfated polysaccharides.…”
Section: Introductionmentioning
confidence: 99%